CASE STUDY: APPLICATION OF KEGEL EXERCISES IN REDUCING MICTURITION INTENSITY - Dessy Hidayati Fajrin; Yeni Muliani (Jurnal Medicare, 2024)
The discomfort in pregnant women is the increased intensity of urination caused the uterus that pushed forward so that the bladder feels full. The way to deal with this discomfort is by doing Kegel exercises. This exercise serves to train and strengthen the pelvic muscles. This can help pregnant women control their bladder and reduce the frequency of urination. The purpose of this study was to provide midwifery care for pregnant woman on third trimester with Kegel exercise to overcome the problem of increasing the intensity of urination at night. This study used a qualitative research method in the form of a case study using a Varney management midwifery care approach. The research subjects used were Mrs. W with complaints of increased intensity of urination at night. The research was conducted for 14 days at UPT Puskesmas Selakau, Sambas. The results showed that the intensity of urination decreased after doing 10 repetitions of Kegel exercises and doing them 3 times a day. It can be concluded that Kegel exercise therapy can help overcome the problem of frequent urination. Advice that can be given to pregnant women to overcome the problem of frequent urination is to do Kegel exercises regularly.